Medical Education for the 21st Century - Firstenberg, Michael S.; Stawicki, Stanislaw P. (IntechOpen, 2022)
Medical education has undergone a substantial transformation from the traditional models of the basic classroom, laboratory, and bedside that existed up to the late 20th century. The focus of this text is to review the spectrum of topics that are essential to the training of 21st-century healthcare providers. Modern medical education goes beyond learning physiology, pathophysiology, anatomy, pharmacology, and how they apply to patient care. Contemporary medical education models incorporate multiple dimensions, including digital information management, social media platforms, effective teamwork, emotional and coping intelligence, simulation, as well as advanced tools for teaching both hard and soft skills. Furthermore, this book also evaluates the evolving paradigm of how teachers can teach and how students can learn - and how the system evaluates success.